SEARCH FOR CONTINUOUS IMPROVEMENT THROUGH THE APPLICATION OF 5S IN A LABORATORY IN THE SUGAR ENERGY SECTOR - Furtado, Andreina Ester Aparecida Alcides; Guimaraes, Camila Carla (Revista Interface Tecnológica, 2024)
The use of quality tools plays a crucial role in promoting the continuous improvement of organizational processes, being indispensable for companies that aim to maintain their competitiveness. This article focuses on presenting the results of the implementation of the 5S methodology in a laboratory within the sugar-energy sector. The research, conducted through a case study, evaluated the changes resulting from the application of this methodology. The study demonstrated that 5S was effective in optimizing laboratory processes, reducing waste, and increasing productivity, in addition to significantly contributing to the organization, cleanliness, and safety of the work environment. Despite initial challenges, the observed benefits confirm the relevance of the topic addressed. It is concluded that, when consistently applied, 5S is a powerful tool for driving continuous improvement.
Keywords: Management; Quality tools; Sugar-energy laboratory; Agribusiness